2021
DOI: 10.20473/imhsj.v5i2.2021.209-219
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Post Partum Depression on the Seventh Day Puerperium

Abstract: Background: Postpartum depression is a psychological disorder during the postpartum period which is more dangerous than the baby blues. Postpartum depression can have a serious impact on the development of the baby as well as the social life of the mother. To anticipate the incidence of postpartum depression, it is necessary to have early detection. The purpose of this study was to describe the results of the seventh day postpartum depression screening at PMB S Malang City. Methods: The design of this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this study it was found that Post SC showed more psychological disorders, in husbands (13). The link between perceptions of social support and feelings of depression was examined in a study conducted in Istanbul, Turkey.…”
Section: Postmentioning
confidence: 86%
“…In this study it was found that Post SC showed more psychological disorders, in husbands (13). The link between perceptions of social support and feelings of depression was examined in a study conducted in Istanbul, Turkey.…”
Section: Postmentioning
confidence: 86%